Penegakan hukum di Indonesia - Fawzy, Hamida Rizka; F, Jesselyn; N, Andi; Khulfah, Ahmad Arrosi (Maliki Interdisciplinary Journal, 2024)
In a nation or country, there is a great need for a legal policy that can regulate all actions or activities in a country. In the process of law enforcement in Indonesia of course requires the role of the people and the Indonesian government apparatus itself in order for a law to be properly and properly enforced. If there is a problem with a law, then the source of the problem is the law enforcement, which does not implement the provisions of the law as it should be, or the society that does not understand how the law is implemented. Of the various problems of a law there must be an effort in solving the problem to realize justice and order in enforcing a law.